Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Café Janji Jiwa Siswa Kampung Baru Di Kota Sorong - Olyvia Magdalena Pandelawang; Farsis A Laisoka; Dovita Y.M Talaen (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
The problem being studied is whether there is an effect of product quality and service quality on customer satisfaction at the Janji Jiwa Siswa Kampung Baru Café in Sorong City. This study aims to analyze and prove the influence between the independent and dependent variables in this study. In this research is causal research, researchers used 72 samples from customers of Café Janji Jiwa. How to collect data using a questionnaire and the answers using a four-gradation Likert scale. How to take the sample using Purposive Random Sampling. The analysis tool used is Multiple Linear Regression from each short answer that is expanded in the sub-chapters below in full. In this study using a quantitative approach. Data collection method used is the distribution of questionnaires. Test Instruments in this study used validity and reliability tests equipped with classic assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests, while data analysis was performed using multiple linear regression analysis. The research results show that product quality has the most dominant influence with a beta value of and with a sig value of 0.000 while service quality has the smallest influence on customer satisfaction, namely with a beta value of and a sig value of. This shows that product quality plays an important role in determining customer satisfaction.